Analisis Yuridis Peraturan Gubernur Riau Nomor 14 Tahun 2021 Tentang Penerimaan Peserta Didik Baru pada Jenjang Sekolah Menegah Atas Negeri dan Sekolah Menengah Kejurusan Negeri Serta Pendidikan Khusus di Provinsi Riau - Rismahayani Rismahayani (Departement of Mathematics Education, 2023)
In realizing equal distribution of education in accordance with the constitutional mandate of the 1945 Constitution and Law Number 20 of 2003 concerning the National Education System, the government has since 2017 implemented a